Off-grid photovoltaic system design for on-board blue swimming crab streamer processing and cold storage: System design and simulation - Kuncoro Ari; Setiawan Ahmad Agus; Natsir Moh; Wisnugroho Susilo; Sasmita Suparman; Setiyobudi Nanang; Zarochman; Sukoraharjo Sri Suryo; Wassahua Zainal; Permana Sofiyan Muji; Sari Rodiah Nurbaya; Nugroho Kuncoro Catur; et al. (BIO Web of Conferences)
Blue swimming crab (BSC) catch is considered a highly perishable product; initial on-board processing, including steaming and cool preservation, is necessary to maintain quality. Traditionally, a fire stove conducts the BSC steaming process; this can pose a fire hazard on a wooden boat. Further, the ice-cooled boxes stored the steamed BSC, which could melt and seep into the BSC meat. As an innovation, we could change the BSC steaming process using electronic devices such as electronic stoves and cooling preservation using electric cold storage; both alternatives require electricity as a power source. One electricity source is converting solar energy using solar panel systems (PV). This research aims to design a PV system for the initial on-board processing of BSC and storage, using simulations with PVsyst 7.2 software, to serve as a reference for fishermen, entrepreneurs, and relevant stakeholders. A quantitative method generates wiring diagrams, installation diagrams, and placement plans for the photovoltaic (PV) system and electronic equipment. The technical and economic analyses determined the viability of utilizing the photovoltaic system design. The research result was a complete off-grid PV system design, producing 1740 kWh/year of electricity with a specific yield of 1450 kWh/kWp/year. The investment in the off-grid PV system reaches the break-even point in 2043, with a profit of 68,534 IDR. This off-grid PV system design can supply the electricity needed for electronic equipment used in the initial on-board processing of BSC catch.